Systemic Sclerosis with Multiple Pulmonary Manifestations - MOHAN RAO KOTNUR; PARINITA SURESH; VENKATA SIVA PRASAD REDDY; TARUN SHARMA; NABIL AHMED SALIM (Journal of Clinical and Diagnostic Research, 2016)
Systemic sclerosis (SSc) is a chronic autoimmune multisystem disorder characterized by endothelial dysfunction and fibroblast dysfunction, which results in progressive fibrosis of the skin and internal organs more frequently the lungs and gastro intestinal tract. Pulmonary involvement is common in the course of SSc, with Interstitial Lung Disease (ILD) and Pulmonary Arterial Hypertension (PAH) being the leading causes of death. Here we report, case of an elderly female patient presenting with Diffuse SSc with multiple uncommon pulmonary manifestations like ILD with Usual Interstitial Pneumonia (UIP) pattern (usually less common), PAH and right sided pleural effusion.